Analisis Kualitas Bakteriologis (E.Coli dan Coliform) Air Minum Isi Ulang (Amiu) Di Kecamatan Lolak Kabupaten Bolaang Mongondow - Arafah Bandu; Thelma D. J Tuju; Jan R. Assa (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
This research uses descriptive analysis method in order to know the content of microorganisms E.coli and Coliform in refill drinking water at several refill drinking water depots in Lolak sub-district, Bolaang Mongondow regency. The results of the study on the analysis of E. coli microorganisms from eight water samples tested, namely D1, D2, E1, E2, F1, F2, G1, G2 all met the requirements determined by the Indonesian National Standard (SNI) and PERMENKES No. 492 of 2010. While in terms of the Coliform test, it is found that there is only one sample of water that is not fit for consumption, which is in the sample code G2 where the amount of Coliform contained in it exceeds the amount determined by the Indonesian National Standard (SNI) while the other samples, with sample codes D1, D2, E1, E2, F1, F2, G1 meet the requirements of the Indonesian National Standard (SNI) for consumption. Keywords: refill drinking water; E.coli; Coliform.